(untitled) (Dhaka University Law Journal, 2026)
This article reconstructs how “marriageable age” in Hindu law was made across doctrinal, institutional, and evidentiary registers. It traces the shift from a guardianship- centred kanyādāna framework, where puberty and household competence acted as proxies, to a modern regime organised around consent and statutory majority. Colonial change proved pivotal: the fabrication of “Anglo-Hindu law”, the move from paṇḍit-assisted adjudication to High Court precedent, and proof rules under the Indian Evidence Act 1872 together made age a justiciable fact. Criminal-law overlays, including the marital rape exception and the Age of Consent Acts 1891 and 1925, were stress-tested in litigation and fed into the civil age conditions of the Sarda/Child Marriage Restraint Act. Contemporary trajectories in India, Nepal, Pakistan, Sri Lanka, and Bangladesh expose the structural effects of registration design and “special-circumstances” waivers. The article concludes with a proportionate reform template and a research agenda grounded in registries, court files, and enforcement records. Dhaka University Law Journal, 2025, 36(2), 23-52